PENGENALAN DAN PELATIHAN MENGENAI PROFESSIONAL ETHICS DAN SOCIAL RESPONSIBILITIES FOR HOSPITALITY AND TOURISM [INTRODUCTION AND TRAINING ON PROFESSIONAL ETHICS AND SOCIAL RESPONSIBILITIES FOR HOSPITALITY AND TOURISM] - Juliana Juliana; Rudy Pramono; Rosianna Sianipar; Febryola Indra (Universitas Pelita Harapan, 2021)
Community service is an undertaking that involves exchanging information and expertise in order to increase a feeling of caring for the local community. The goals of community service programs are to (1) exchange students' expertise and skills through courses at Pelita Harapan University's Faculty of Tourism, and (2) to give back to the community. (2) To train human capital for professional careers, especially in the hospitality and tourism industries, in the Normal period. (3) To put the expertise and skills acquired by students at Pelita Harapan University's Faculty of Tourism to use. This activity was attended by 323 respondents spread across several universities in Indonesia, which took place virtually. Therefore, the Community Service team created a community service activity program in the form of a webinar. It is hoped that this activity can be helpful for students / the general public and be developed in the future. With this webinar, participants can get an overview of professional ethics and social responsibility in hospitality and tourism and can apply it in the professional world. BAHASA INDONESIA ABSTRACT: Dedikasi kepada warga merupakan aktivitas yang dicoba buat tingkatkan rasa hirau warga dekat dengan metode memberikan ilmu ataupun keahlian kepada warga dekat.( 1) Memberikan pengetahuan serta keahlian yang dipunyai oleh mahasiswa lewat mata kuliah di Fakultas Pariwisata, Universitas Pelita Harapan,( 2) Mempersiapkan sumber energi manusia buat merambah dunia practitioner paling utama bidang perhotelan serta pariwasata( 3) Buat mengaplikasikan ilmu serta pengetahuan yang diperoleh mahasiswa lewat riset di Fakultas Pariwisata, Universitas Pelita Harapan. Kegiatan ini diikuti oleh 323 responden yang tersebar pada beberapa perguruan tinggi di Indonesia yang berlangsung secara virtual. Oleh karena itu, tim Pengabdian kepada Masyarakat membuat program kegiatan pengabdian kepada masyarakat dalam bentuk webinar. Diharapkan kegiatan ini dapat bermanfaat bagi mahasiswa/masyarakat umum dan dapat dikembangkan di masa depan. Dengan webinar ini para peserta dapat mendapatkan gambaran mengenai etika profesi dan tanggung jawab sosial di dunia perhotelan dan pariwisata serta dapat mengaplikasikannya di dunia professional.